An Experimental Study to Evaluate the Thermal Performance of Composite Trombe Wall in Passive Solar Heating and Cooling - كنجو, لانا; نجار, قمر الزمان (Latakia University Journal -Engineering Sciences Series, 2021)
This research presents an experimental study of the performance of storage Trombe wall in Lattakia. To do that, three experimental models of (1 × 1 × 1 [m]) size for each were designed. The first one represents a reference test room that simulates a normal, isolated house. The southern façade of the second model was designed to simulate classic Trombe wall, while the southern façade of the latter was designed to simulate composite Trombe wall. The temperature was measured within these models, and the thermal performance was evaluated during summer and winter. The results showed that composite Trombe wall was the best of all, as the difference between its temperature and the ambient temperature was about during summer, and about during winter time. The influence of some parameters that can affect the performance of composite wall was also studied. The results showed that the optimum values for the best thermal performance of the composite Trombe wall were for a thickness of 2 [cm] for the gap between the glass and the massive wall, and for a thickness of 4 [cm] for the gap between the insulating wall and massive wall.